The The Effect of Document Holder’s Degree of Tilt on Working Speed and Fatigue - Christian Palit, Herry; Yang Aysia, Debora Anne (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
The prolonged use of computer s , followed by incorrect posture, could cause neck pain and excessive eye refocusing. Document holder was one of office ergonomics’ tools that could reduce neck pain and eye refocusing problems. The research aims to find out the optimum document holders’ degree of tilt. Twenty female respondents from Faculty of Industrial Technology conducted typing activity using a document holder. There were three document holder’s tilt angle levels: 15°, 30°, and 45°. The responses of this study were working speed and fatigue’s level that have lower the better characteristics. Indicators of fatigue’s level that were being used were reaction time’s difference and eyes fatigue level. Working speed and reaction time difference were analyzed by using Pearson Correlation test and Multivariate Analysis of Variance. Eye fatigue level was analyzed by using Kruskal-Wallis. The results show that the optimal document holder’s degree of tilt is 45°.